Strategies for information technology and intellectual capital challenges and opportunities - Joia (Information Science Reference, 2007)
"This book presents efficient ways for executives to understand the impact of IT on the intellectual capital of their firms, and searches for a new mandate for management that takes into consideration the pervasive role of IT on competitive boundaries. It provides a synopsis of the history, origin, taxonomies, ontologies, measurement models, and dynamics of intellectual capital"--Provided by publisher.